Evaluation of Reference Genes for Quantitative Real-Time PCR Analysis of the Gene Expression in Laticifers on the Basis of Latex Flow in Rubber Tree (Hevea brasiliensis Muell. Arg.) - Chao, Jinquan; Yang, Shuguang; Chen, Yueyi; Tian, Wei-Min (Frontiers in Plant Science, 2016)
Latex exploitation-caused latex flow is effective in enhancing latex regeneration in laticifer cells of rubber tree. It should be suitable for screening appropriate reference gene for analysis of the expression of latex regeneration-related genes by quantitative real-time PCR (qRT-PCR). In the present study, the expression stability of 23 candidate reference genes was evaluated on the basis of latex flow by using geNorm and NormFinder algorithms. Ubiquitin-protein ligase 2a (UBC2a) and ubiquitin-protein ligase 2b (UBC2b) were the two most stable genes among the selected candidate references in rubber tree clones with differential duration of latex flow. The two genes were also high-ranked in previous reference gene screening across different tissues and experimental conditions. By contrast, the transcripts of latex regeneration-related genes fluctuated significantly during latex flow. The results suggest that screening reference gene during latex flow should be an efficient and effective clue for selection of reference genes in qRT-PCR.